2009
DOI: 10.1016/j.ejpain.2008.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Participation of peripheral tachykinin NK1 receptors in the carrageenan‐induced inflammation of the rat temporomandibular joint

Abstract: Temporomandibular disorders represent one of the major challenges in dentistry therapeutics. This study was undertaken to evaluate the time course of carrageenan-induced inflammation in the rat temporomandibular joint (TMJ) and to investigate the role of tachykinin NK(1) receptors. Inflammation was induced by a single intra-articular (i.art.) injection of carrageenan into the left TMJ (control group received sterile saline). Inflammatory parameters such as plasma extravasation, leukocyte influx and mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 62 publications
2
37
0
3
Order By: Relevance
“…Surgical disruption to physiological structures, including bite raise, severance of the bilaminar zone, or induced condyle hypermobility, leads to inflammatory changes and subchondral bone degeneration in the TMJ (Mao et al, 1998;Sharawy et al, 2003;Yamaza et al, 2003;Embree et al, 2011). TMJ inflammation can also result from injection of chemical irritants, including carrageenan (Denadai-Souza et al, 2009), ovalbumin (Habu et al, 2002), and complete Freund's adjuvant (CFA) (Kerins et al, 2004;Wu et al, 2010;Kou et al, 2011). CFA is a solution of antigen emulsified in mineral oil and consists of inactivated and dried mycobacteria.…”
mentioning
confidence: 99%
“…Surgical disruption to physiological structures, including bite raise, severance of the bilaminar zone, or induced condyle hypermobility, leads to inflammatory changes and subchondral bone degeneration in the TMJ (Mao et al, 1998;Sharawy et al, 2003;Yamaza et al, 2003;Embree et al, 2011). TMJ inflammation can also result from injection of chemical irritants, including carrageenan (Denadai-Souza et al, 2009), ovalbumin (Habu et al, 2002), and complete Freund's adjuvant (CFA) (Kerins et al, 2004;Wu et al, 2010;Kou et al, 2011). CFA is a solution of antigen emulsified in mineral oil and consists of inactivated and dried mycobacteria.…”
mentioning
confidence: 99%
“…In rodent models of arthritis induced by complete Freund's adjuvant or CGN, substance P is a potent mediator of increased microvascular permeability and leukocyte influx via activation of NK 1 receptors located on postcapillary endothelial cells [8,17,39]. However, the allodynia seen in CGN-induced temporomandibular joint arthritis was not affected by the blockade of NK 1 receptors [17], so the role of peripheral substance P in joint pain is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Synovial lavage fluid samples (20 µl) were thawed, and MPO activity was measured as an index of migration of activated polymorphonuclear (PMN) cells to the joint, as previously described [15,16,17]. For this purpose, samples were incubated with tetramethylbenzidine (1.6 m M ), NaPO 4 (80 m M ) and hydrogen peroxide (H 2 O 2 ; 0.3 m M ), and absorbance was read at 650 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One method, von Frey fi laments, described by Maximilian von Frey in 1896, has been used with relative safety and repeatability for the evaluation of cutaneous sensitivity in horses (REDUA et al, 2002;OLESKOVICZ et al, 2006) and dogs (DUQUE et al, 2004, KUKANICH & PAPICH, 2011. As an alternative to the von Frey fi laments, electronic methods have been developed and tested on other species (CUNHA et al, 2004;DENADAI-SOUZA et al, 2009) and showed advantages over the classic method, including a reduction in the number of attempts required to evaluate the nociceptive threshold, the elimination of problems in the standardization of the fi laments.…”
Section: Introductionmentioning
confidence: 99%